1998
DOI: 10.1007/s002340050564
|View full text |Cite
|
Sign up to set email alerts
|

Giant arachnoid granulation mimicking dural sinus thrombosis in a boy with headache: MRI

Abstract: We report MRI and angiographic findings of an unusual giant arachnoid granulation in the left sigmoid sinus in a boy with headache. Its signal intensity was lower than that of cerebral cortex on T1-weighted images and higher on T2 weighting, mimicking dural sinus thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 5 publications
1
35
0
Order By: Relevance
“…In the contrast-enhanced CT images in the article published by Kan et al, 9 intrinsic vessels within the granulation are also well seen, though not described in the text. In a report by Chin et al, 10 demonstration of internal flow voids was identified in a left TS AG, compatible with venous channels. Farb 11 describes a displaced eccentric internal vein in 97% of AGs greater than 4 mm in diameter by using high-resolution CE-MRV.…”
Section: Discussionmentioning
confidence: 82%
“…In the contrast-enhanced CT images in the article published by Kan et al, 9 intrinsic vessels within the granulation are also well seen, though not described in the text. In a report by Chin et al, 10 demonstration of internal flow voids was identified in a left TS AG, compatible with venous channels. Farb 11 describes a displaced eccentric internal vein in 97% of AGs greater than 4 mm in diameter by using high-resolution CE-MRV.…”
Section: Discussionmentioning
confidence: 82%
“…We refer to arachnoid granulation as "giant" when it is of sufficient size to fill the lumen of a dural sinus and cause local dilatation or filling defect 7) . Although giant arachnoid granulations are sometimes discovered as an incidental finding in the transverse and posterior superior sagittal sinus 1,3,10) , they rarely cause symptoms of increased intracranial pressure from venous hypertension secondary to partial sinus occlusion 1) . If symptoms present, intrasinus pressure measurements across the lesion through each dural sinus can be used to determine whether the lesion is causing venous outflow obstruction and venous hypertension 7) .…”
Section: Discussionmentioning
confidence: 99%
“…The typical MRI findings of dural sinus thrombosis are an iso-to hyperintense blood clot in the sinus on T1WI which is hyperintense on T2WI 4) . The key MRI features of giant arachnoid granulations are non-enhancing granules with central linear enhancement and surrounding enhancing flowing blood on contrast-enhanced MR venography 3) . Intrasinus thrombus may show contrast enhancement and occlude venous flow.…”
Section: Discussionmentioning
confidence: 99%
“…Arachnoid granulations are most frequently reported as incidental findings on angiography, contrast enhanced CT or MR imaging [22,142]. The true incidence and range of variation of 'normal' arachnoid granulations in a large series of asymptomatic individuals is yet to be established.…”
Section: Venous Sinus Obstruction In Pseudotumor Cerebri Syndromementioning
confidence: 99%